Cognitive processes and problem-solving strategies: the effect of the teacher training program "Teaching to Think" in relation to early thinking - Noriega Noriega, Huberto Rafael
The teaching training program "Enseñando a Pensar" was applied to 70 teachers from educational institutions of the department of Atlántico, who were evaluated through questionnaires after the training they received. On the other hand, the processes and strategies used by their students were evaluated. These results showed that the final results of this study refer to the Pedagogical Knowledge of the Content related to the cognitive processes and problem solving strategies of additive structures, in the better performance of their students in the solution of problems, showing the effectiveness of the program.